Project management for archaeology - Vilanova, Rodrigo (Portfolio and project management collection, 2017)
Archaeology, the science in charge of studying ancient cultures, is without a doubt one of the most alluring professions in today's academic world. It is a versatile and complex discipline requiring a lot of skill expertise from both students and specialists, including the efficient management of team of coworkers, logistics, resources, etc. Project Management for Archaeology is a first approach to students and inexperienced archaeologists striving to better organize, lead, and execute an archaeological project. It also offers great insight and strategies to experienced and "old-school" researchers in order to improve efficiency, leadership, and organizational skills, following the most effective management techniques in the market. Presented with a flexible approach that accommodates all types of archaeological research (from academic to rescue and salvage projects), Project Management for Archaeology is meant to be a practical handbook to be used all along the lifetime of any archaeological project.